OPTIMALISASI KINERJA SATLANTAS POLRES DEMAK DENGAN MENGGUNAKAN SIM ONLINE UNTUK MENINGKATKAN PELAYANAN PRIMA - dimpos tampubolon (Indonesian Journal of Police Studies, 2022)
ABSTRACT PERFORMANCE OPTIMIZATION OF DEMAK POLICE SATLANTAS BY USING ONLINE SIM TO IMPROVE PRIMARY SERVICE Dimpos Barmawi Tampubolon, 18.007, dimpostampubolon@gmail.com Human life is dynamic, encouraging the development of the social life sector. Development causes changes in positive / negative impacts. The development of means of transportation continues to this day. To reduce the negative impact of means of transportation, the National Police is authorized to issue a Driving Permit/SIM to a person who meets the administrative requirements, is physically and mentally healthy, understands traffic regulations and is skilled or passes a motorized vehicle driving test. SIM Function Article 86 of Law Number 22 Year 2009 concerning Road Traffic and Transportation. The National Police, through the Satlantas Regident unit, seeks to fulfill SIM ownership rights. Increasing public services will create public trust in the Police. Optimization of online SIM services must meet current standards. The correct use of technology will reduce direct interaction between the community and the officers so as to minimize the occurrence of illegal fees for SIM services. Police modernization does not only rely on existing technology but the quality of Polri's human resources to provide services, protection and protection to the community. The purpose of this study was to determine the implementation of online SIM services at the Demak Police Station and to optimize the performance of the Demak Police Traffic Unit to improve the excellent online SIM service. This research uses Public Service Theory, Management Theory, SWOT Analysis Theory, Optimization Concept, MIS Concept, Online Concept. Descriptive research method, research location Satlantas Polres Demak. Data analysis using interview results, relevant documents. The online SIM service at the Demak Police Station is quite good by utilizing internet technology to the maximum, the personnel provide friendly service so that the community is happy, the facilities and infrastructure are in good condition and the community appreciates it. The inhibiting factor at Polres Demak is also almost the same as in other Polres areas: Systematic network disruption from Korlantas so if there is a server down as a result the online SIM process will stop. Optimizing the performance of online SIM services at the Demak Police Station as an effort to maximize service has been going well. Changes in modern police technology In the Police 4.0 Era actively provide education to the community, especially the Demak area in order to increase public trust in the community. It is hoped that the SINAR application can soon be implemented throughout Indonesia in order to maximize online SIM services. Keywords: Optimization, Service, SIM Online.